Butch Wilkins and the Sundance Kid A Teenage Obsession with TV Sport. - Tassell, Nige (Birlinn, Limited, 2018)
Butch Wilkins and the Sundance Kid charts, both hilariously and touchingly, sport's golden years on terrestrial television, recreating the halcyon days of 1980s British sport.